Role of granulosa cell mitogen-activated protein kinase 3/1 in gonadotropin-mediated meiotic resumption from diplotene arrest of mammalian oocytes. (4th March 2018) - Sahu, Kankshi; Gupta, Anumegha; Sharma, Alka; Tiwari, Meenakshi; Pandey, Ashutosh N.; Prasad, Shilpa; Yadav, Pramod K.; Pandey, Ajai K.; Shrivastav, Tulsidas G.; Chaube, Shail K.
Abstract: In mammals, preovulatory oocytes are encircled by several layers of granulosa cells (GCs) in follicular microenvironment. These follicular oocytes are arrested at diplotene arrest due to high level of cyclic nucleotides from encircling GCs. Pituitary gonadotropin acts at the level of encircling GCs and increases adenosine 3′, 5′-cyclic monophosphate (cAMP) and guanosine 3′, 5′-cyclic monophosphate (cGMP) and activates mitogen-activated protein kinase 3/1 (MAPK3/1) signaling pathway. The MAPK3/1 disrupts the gap junctions between encircling GCs and oocyte. The disruption of gap junctions interrupts the transfer of cyclic nucleotides to the oocyte that results a drop in intraoocyte cAMP level. A transient decrease in oocyte cAMP level triggers maturation promoting factor (MPF) destabilization. The destabilized MPF finally triggers meiotic resumption from diplotene arrest in follicular oocyte. Thus, MAPK3/1 from GCs origin plays important role in gonadotropin-mediated meiotic resumption from diplotene arrest in follicular oocyte of mammals.